Pengaruh Aktivitas Renang Terhadap Keseimbangan dan Koordinasi Motorik Anak Usia Dini pada Kegiatan Ekstrakurikuler di SDK Marsudirini - Negara, Gusti Agung Ayu Komang Ari Natasya Sastra; Dewi, Komang Ayu Krisna; Indrawan, I Ketut Addy Putra; Ilmawan, Anggo Widcaksana; Rusmayani, Ni Gusti Ayulia; Ginanjar, Agi; Harmajudha, Marcus Christiawan (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of swimming activities on the development of balance and motor coordination in early childhood at SDK Marsudirini, Jembrana Regency. The research method used was quasi-experiment with *non-equivalent control group* design. The sample consisted of 42 early childhood students, which were divided into experimental groups (n = 21) and control groups (n = 21). The research instruments were balance and motor coordination tests conducted at pre-test and post-test. The data were analyzed using quantitative descriptive methods. The results of the paired t-test showed significant improvement in the experimental group in both aspects of balance (pre-test: 12.3 ± 1.8; post-test: 17.8 ± 2.0; p = 0.000) and motor coordination (pre-test: 14.5 ± 2.1; post-test: 19.6 ± 2.4; p = 0.000). In contrast, the control group showed no significant changes in either aspect. The independent t-test also showed significant differences between the experimental and control groups in the post-test results of balance (p = 0.000) and coordination (p = 0.000). These findings confirm that swimming activities can significantly improve balance and motor coordination in early childhood, so it can be used as one of the recommended educational approaches in children's physical education programs.